Development of PBL-Based Interactive LKPD to Improve Elementary Students’ Critical Thinking Skills in Science Learning - Suradi, Suradi; Prastowo, Srihandono Budi; Sutomo, Moh. (Jurnal Paedagogy, 2024)
This research aims to develop PBL-based interactive worksheets that can improve the critical thinking skills of elementary school students in science learning that are valid, practical and effective when used. This research used the Design and Development (D&D) method using the ADDIE model, which consists of five stages consisting of analysis, design, development, implementation and evaluation. The research subjects for the limited test were 30 students in class VI at SDN 3 Rogojampi. In the broad test, there were 42 students in class VI at SDN 1 Pengatigan and 32 students in class VI at SDN 2 Rogojampi. The instruments used consisted of 1) an RPP validation sheet, 2) an LKPD validation sheet, 3) a teacher response questionnaire sheet, and 4) student pretest-posttest questions to assess the effectiveness of the LKPD. The data analysis technique used was data analysis of the validity, effectiveness and practicality of the product being developed. The results of the validation by the material expert validator were 93%, the media expert validator was 91%, and the language expert validator was 91%. The results of the effectiveness of using interactive LKPD based on the N-gain score in the three institutions obtained an average score of 0.69, which is in the medium category. Practical results based on the implementation of the use of interactive worksheets obtained an average of 90% and, based on teacher responses, obtained an average of 91% in the very practical category. This study concludes that PBL-based interactive worksheets are valid, very practical and moderately effective for improving the thinking skills of sixth-grade elementary school students in science learning.